OPTIMALISASI SDM DALAM MENINGKATKAN KINERJA DAN KEBERLANJUTAN BAGI KOPERASI PEMBERDAYAAN UMMAT DAARUT TAUHID - Rahmayanti Tumanggor; Styo Budi Utomo; Rizka Wahyuni Amelia (Abdi Jurnal Publikasi, 2025)
Cooperatives play a vital role in building the people's economy, yet many cooperatives face challenges in human resource (HR) management. This community service program aims to optimize the role of HR in improving the performance and sustainability of the Daarut Tauhid Community Empowerment Cooperative. The method used was a participatory approach through competency mapping, managerial training, and mentoring in the development of standard operating procedures (SOPs). The results of the activity demonstrated an increased understanding of managerial roles, improved organizational communication, and management initiatives in improving work systems. This activity reinforces the importance of the human capital approach and the Resource-Based View (RBV) in cooperative development. It is hoped that cooperatives can continue to develop their HR independently to achieve more optimal and sustainable performance.